Compatibilizando direitos sociais com competitividade: Fiscais do trabalho e a implementaç\~ao da legislaç\~ao trabalhista no Brasil - Roberto Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This paper addresses the following question: how can we reconcile workers` rights and social protection with firms` competitiveness and productivity? In Latin America, there is an intense debate about the perverseness of the labor law (claimed to be harmful both to workers and to firms) and, in response, current policy advice emphasizes deregulation and the flexibilization of existing labor rights. In contrast to the standard policy advice, this research demonstrates that there are more degrees of freedom to reconcile workers` rights with competitiveness when one focuses on the implementation of the labor law. I investigated the street-level work performed by labor inspectors in two Brazilian states (Minas Gerais and Bahia) and I found out that in some cases labor inspectors have been able to implement labor law in a way that promotes both the improvement of working conditions as well as firm upgrading. My findings suggest that labor inspectors have been able to promote these outcomes-such as alternative arrangements for formally hiring short-term rural workers or technical measures to promote safer working conditions without jeopardizing firm`s productivity, for example-by combining both punitive (e.g., fines, sanctions) with pedagogical (e.g., technical and legal assistance) enforcement strategies. For a list of the cases as well as their respective outcomes, please refer to chart 1 and 2.
Keywords: J88; K42; K32; 330; Arbeitsrecht; Arbeitsschutz; Arbeitsschutz; Brasilien; Minas Gerais; Bahia